A Reference Point for Designing a Cybersecurity Curriculum for Universities - (:unkn) unknown (My University, 2021)
The objective of this study is to propose a cybersecurity curriculum from a best practice perspective for universities and other higher educational institutions. Cybersecurity is a fast-growing part of the overall job market and cybersecurity skills shortage is a factor that needs attention worldwide. An updated approach is needed to build the cybersecurity labour force. A scoping literature review was applied on academic databases for proposed cybersecurity skills curricula. It was also applied on cybersecurity curricula offered by top universities as well as by studying cybersecurity curriculum frameworks and guidelines. The knowledge, skills, abilities and modules from the aforementioned were integrated to compile a holistic reference point for a cybersecurity curriculum. The study found that there is a global need for cybersecurity degrees and specifically for African countries like South African. More cybersecurity professionals need to be trained in the necessary technical abilities, combined by the necessary soft skills to be productive and fill the gaps in industry. This is possible by concentrating on this study’s proposal namely a reference point for cybersecurity modules to be included in a cybersecurity curriculum.
Keywords: African Research